Persistent hypertriglyceridemia in statin-treated patients with type 2 diabetes mellitus - Feher, Michael (Dove Medical Press, 2013)
PURPOSE: This paper reports the results of an audit that assessed the prevalence of residual hypertriglyceridemia and the potential need for intensified management among patients with statin-treated type 2 diabetes mellitus (T2DM) in primary care in the UK. PATIENTS AND METHODS: A cross-sectional, observational, systematic audit of patients with diagnosed diabetes from 40 primary care practices was undertaken. The audit collected basic demographic information and data on prescriptions issued during the preceding 4 months. T2DM patients were stratified according to the proportion that attained European Society of Cardiology treatment targets. RESULTS: The audit collected data from 14,652 patients with diagnosed diabetes: 89.5% (n = 13,108) of the total cohort had T2DM. Of the people with T2DM, 22.2% (2916) were not currently receiving lipid-lowering therapy. Up to approximately 80% of these people showed evidence of dyslipidemia. Among the group that received lipid-lowering therapy, 94.7% (9647) were on statin monotherapy, which was usually simvastatin (69.5% of patients receiving statin monotherapy; 6707). The currently available statins were prescribed, with the most common dose being 40 mg simvastatin (44.2%; 4267). Irrespective of the statin used, around half of the patients receiving statin monotherapy did not attain the European Society of Cardiology treatment targets for triglycerides, low-density lipoprotein, high-density lipoprotein, and total cholesterol. CONCLUSION: T2DM patients managed in UK primary care commonly show persistent lipid abnormalities. Clinicians need to optimize compliance with lipid-lowering and other medications. Clinicians also need to consider intensifying statin regimens, prescribing additional lipid- modifying therapies, and specific treatments aimed at triglyceride lowering to improve dyslipidemia control in statin-treated patients with T2DM.